Experimental Study on Sediment Control in a Lateral Intake Channel by Using a Spur Dike Combined with a Skimming Wall - Amir Moradinejad; Amir Hamzeh Haghiabi; Mojtaba Saneie; Hojjatallah Younesi (Advances in Civil Engineering and Environmental Science)
Water diversion using lateral intakes often leads to the issue of sediment entering water transmission systems. Failure to control sediment at the intake results in its transfer into irrigation canals and facilities, causing numerous problems in various parts of the system. To address this, a range of structures, such as submerged vans, sills, spur dike, skimming walls, and their combinations, are employed to manage sediment in intakes. In this study, the effects of skimming walls and spur dike positioned at four distances (b, 2b, 2.5b, and 3b, where b is the width of the intake channel) and four angles (30°, 45°, 60°, and 90°) on sediment control and water intake efficiency were investigated experimentally. The results revealed that a spur dike positioned at an angle of 60° and a distance of 2b from the center of the inlet opening demonstrated superior performance. Specifically, it reduced sediment by 27%, 14%, and 12% while increasing the diverted discharge to the inlet by 53%, 45%, and 16% compared to angles of 30°, 45°, and 90°, respectively. Additionally, a 5% increase in the ratio of average flow velocity to the equivalent movement threshold velocity led to a 47% decrease in inlet discharge and a 120% increase in sediment entering the inlet.